PROSES BERPIKIR SISWA MADRASAH ALIYAH DALAM MEMBUAT PETA KONSEP TURUNAN DİTİNJAU DARI GAYA BELAJAR VISUAL, AUIDITORI DAN KINESTETIK - Ahmad Isro'il; Sukiyanto; Pujiono (CENDEKIA, 2020)
This research aims to describe the thinking process of students in creating concept maps based on visual, auditory and kinesthetic learning styles.This research is descriptive research with qualitative approach. The subjects consisted of 3 students based on the learning style questionnaire analysis. Data collection techniques are job-based interviews.The results showed that there are differences in students' thinking processes in creating concept maps. The three subjects perform the stage of creating a concept map completely but there are differences on how to make it. This happens because subjects with an auditory learning style can’t make a cross link so the resulting concept maps are different.The results of this research can be used as an alternative in developing learning by concept map method.